2019
DOI: 10.3390/genes10120982
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Genes Involved in Anthocyanin Biosynthesis and Accumulation in Taxus chinensis

Abstract: Taxus chinensis is a precious woody species with significant economic value. Anthocyanin as flavonoid derivatives plays a crucial role in plant biology and human health. However, the genes involved in anthocyanin biosynthesis have not been identified in T. chinensis. In this study, twenty-five genes involved in anthocyanin biosynthesis were identified, including chalcone synthase, chalcone isomerase, flavanone 3-hydroxylase, anthocyanidin synthase, flavonoid 3’-hydroxylase, flavonoid 3’,5’-hydroxylase, dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…This was similar to the results of anthocyanin biosynthesis in torenia ( Torenia fournieri Lind.) and Taxus chinensis [ 30 , 31 ]. The UFGT gene plays a vital role in the synthesis and the final step of the accumulation of anthocyanins, and it is gradually activated along with the fruit coloring period [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the results of anthocyanin biosynthesis in torenia ( Torenia fournieri Lind.) and Taxus chinensis [ 30 , 31 ]. The UFGT gene plays a vital role in the synthesis and the final step of the accumulation of anthocyanins, and it is gradually activated along with the fruit coloring period [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of expression of PAL, CHI, 4CL, F3H, and UFGT were the same in the solanaceous black nightshade ( Solanum nigrum Linn.) (Saophea et al, 2020 ), grape ( Vitis vinifera L. × Vitis labrusca L.) berry skin (Wang et al, 2013 ), Taxus chinensis (Zhang et al, 2019 ), and the purple‐head trait of Chinese cabbage ( B. rapa L.) (He et al, 2020 ), which promoted the accumulation of anthocyanins. However, in black and white mulberry ( Morus nigra and Morus alba , respectively), the expression of F3H was upregulated in white and downregulated in black mulberry, which indicated that the expression of F3H inhibited the synthesis of anthocyanin (Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of expression of PAL, CHI, 4CL, F3H, and UFGT were the same in the solanaceous black nightshade (Solanum nigrum Linn.) (Saophea et al, 2020), grape (Vitis vinifera L. Â Vitis labrusca L.) berry skin (Wang et al, 2013), Taxus chinensis (Zhang et al, 2019), and the purple-head trait of Chinese cabbage (B. rapa L.) (He et al, 2020), which promoted the accumulation of anthocyanins.…”
Section: Anthocyanin Content and Related Gene Expression In Purple Po...mentioning
confidence: 99%
“…Wood color is one of the key factors determining the wood quality and economic value of tree plants, especially those used in the furniture, flooring, and other high-value decorative industries [ 1 , 2 ]. “Golden-thread nanmu” is a well-known, highly valuable timber industry product because of its attractive golden color, distinctive fragrance, and durability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%